1996
DOI: 10.1177/002221949602900111
|View full text |Cite
|
Sign up to set email alerts
|

Students with Learning Disabilities in Canadian Colleges and Universities

Abstract: The authors, both of whom are involved in providing support services to university students with learning disabilities, describe some of the current issues and challenges faced by students, staff, and faculty. Programs and initiatives in some Canadian institutions that have proven to be successful are described, such as a sequential five-step procedure model that directed the delivery of services at the university. Resource and reference lists are also provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 2 publications
0
10
0
1
Order By: Relevance
“…To facilitate equal access to education and promote success, universities are required by law to make their services accessible to all people (Mullins & Preyde, 2013). Despite the availability of IMPACT OF ABLEIST MICROAGGRESSIONS 5 additional support (e.g., accessibility centres), several barriers to accessing university services persist (Cox & Klas, 1996;Mullins & Preyde, 2013). In a study of Canadian universities, Hill (1992) found eight disability-related issues that required improvement, including the accessibility of the campus facilities and the attitudes of faculty and staff.…”
Section: Disability In Canadamentioning
confidence: 99%
“…To facilitate equal access to education and promote success, universities are required by law to make their services accessible to all people (Mullins & Preyde, 2013). Despite the availability of IMPACT OF ABLEIST MICROAGGRESSIONS 5 additional support (e.g., accessibility centres), several barriers to accessing university services persist (Cox & Klas, 1996;Mullins & Preyde, 2013). In a study of Canadian universities, Hill (1992) found eight disability-related issues that required improvement, including the accessibility of the campus facilities and the attitudes of faculty and staff.…”
Section: Disability In Canadamentioning
confidence: 99%
“…In Canada, the Learning Disabilities Association of Canada gave a rough estimation that around 10% of students in higher education have some type of LD (including dyslexia) (Cox & Klas, 1996).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Kopp, Miller and Mulkey (1984) report that professors are sometimes unwilling to help because they view the student with a disability as lazy or unmotivated. Hence the attitudes of professors can present a formidable barrier to students with disabilities (Altman, 1981;Cox & Klas, 1996;Haehl, 1989;Siperstein, 1988).…”
Section: Dropping Out Vs Persistingmentioning
confidence: 99%
“…Hill also commented that problems persist in the following areas: (a) identifying those students who require special services; (b) making students aware of the services; and (c) developing fair and equitable admissions policies. Cox and Klas (1996) reported that in Canadian universities attitudinal problems and a general lack of understanding by some faculty and administrators continues. They further state that accommodations for people with disabilities are designed to provide equal opportunity, and that adjustments for them do not jeopardize excellence.…”
mentioning
confidence: 99%